2020
DOI: 10.21203/rs.3.rs-101473/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Source Profiling of Air Pollution and its Association with Acute Respiratory Infections in the Himalayan Bound Region of India

Abstract: The studies related to air pollution and its association with human health over the mountainous region are of utmost importance, and are sparse especially over the Himalayan region of India. This study gives an understanding of increase in the occurrence of respiratory diseases due to the accumulation of pollutants during winter season in the Himalayan region (Kashmir valley). The linkages between various atmospheric variables and clinically validated data have been done using various datasets procured from th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…PM 2.5 can pass through the human body through breathing (inhalation and exhalation) and accumulates in the lungs or trachea, causing severe hazard to human health. A significant number of epidemiological studies have shown that long-term exposure to PM 2.5 can result in respiratory problems, cardiovascular diseases, and lung irritation, hence, the rise in morbidity and mortality. Exposure to PM can cause blood clot, which may eventually lead to heart attack .…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 can pass through the human body through breathing (inhalation and exhalation) and accumulates in the lungs or trachea, causing severe hazard to human health. A significant number of epidemiological studies have shown that long-term exposure to PM 2.5 can result in respiratory problems, cardiovascular diseases, and lung irritation, hence, the rise in morbidity and mortality. Exposure to PM can cause blood clot, which may eventually lead to heart attack .…”
Section: Introductionmentioning
confidence: 99%